2014
DOI: 10.1021/es404325c
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Maternal Transfer of Methylmercury in the Sheepshead Minnow (Cyprinodon variegatus) with an Enriched Mercury Stable Isotope

Abstract: Maternal transfer of methylmercury (MeHg) to eggs is an important exposure pathway for developing offspring. However, our understanding of this process is limited, particularly in estuarine fish. We conducted a 91-day chronic laboratory exposure of Cyprinodon variegatus to four concentrations of dietary MeHg ranging from 0.04 to 9.90 μg g(-1) dw. Juvenile fish were fed a preoogenesis MeHg diet for 28 days, after which the diet was switched to a diet enriched with Me(199)Hg, spanning the period of oogenesis, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Silver eels, which starve during their reproductive migration, may then concentrate stored MeHg, as previously observed for PCB or cadmium in eels (Pierron et al 2008;Van Ginneken et al 2009) and also for different lipophilic compounds, in Pacific salmon during migration to spawning site (Kelly et al 2011). Although, maternal transfer of hydrophobic compounds may be relatively low (Kelly et al 2011;Stefansson et al 2014), concentration processes related to starvation should increase MeHg passed from mother to eggs at the spawning site. We can then hypothesize, as proposed for other species (Trudel and Rasmussen 2006;Swanson et al 2011), that leptocephalus larvae with the faster growth rate and the greater growth efficiency might dilute their Hg burden during oceanic migration.…”
Section: Temporal Variationmentioning
confidence: 65%
See 1 more Smart Citation
“…Silver eels, which starve during their reproductive migration, may then concentrate stored MeHg, as previously observed for PCB or cadmium in eels (Pierron et al 2008;Van Ginneken et al 2009) and also for different lipophilic compounds, in Pacific salmon during migration to spawning site (Kelly et al 2011). Although, maternal transfer of hydrophobic compounds may be relatively low (Kelly et al 2011;Stefansson et al 2014), concentration processes related to starvation should increase MeHg passed from mother to eggs at the spawning site. We can then hypothesize, as proposed for other species (Trudel and Rasmussen 2006;Swanson et al 2011), that leptocephalus larvae with the faster growth rate and the greater growth efficiency might dilute their Hg burden during oceanic migration.…”
Section: Temporal Variationmentioning
confidence: 65%
“…Another origin of MeHg concentration values observed in glass eels might concern maternal transfer, considered as a significant route of exposure for larval and juvenile fish (Alvarez et al 2006). A recent study, conducted in the sheepshead minnow (Cyprinodon variegates) fed a preoogenesis MeHg diet and then a diet enriched with Me 199 Hg during the period of oogenesis, suggested that both female tissue and the maternal diet during oogenesis are significant sources of Hg in eggs (Stefansson et al 2014). Silver eels do not feed during oogenesis (which occurs during their oceanic migration to the Sargasso Sea), but before metamorphosing into silver eels, yellow eels spend a long time in continental waters (4 to 20 years) where they can accumulate high quantities of mercury (Arleny et al 2007;Navarro et al 2013).…”
Section: Temporal Variationmentioning
confidence: 99%
“…For example, the sample size in the high‐dose group was too small to test for statistical significance. Also, consistent with the study's intended purpose, Stefansson et al evaluated egg production and not spawning, hatching, or offspring viability. We included these additional studies in our analysis because they provide information comparable to the studies analyzed by Dillon et al .…”
Section: Trv Derivationmentioning
confidence: 97%
“…In addition, if there are suspicions of water quality problems, a toxicological profile of contaminants in the eggs would be important given that lipid-soluble toxicants can be transferred into oocytes (Ostrach et al . 2008; Stefansson et al . 2014; Sühring et al .…”
Section: Egg Collection and Use Of Thawed Sperm Samplesmentioning
confidence: 99%